2023
DOI: 10.21203/rs.3.rs-2925992/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mediating role of self-compassion in the relationship between psychological flexibility and psychological well-being in women with breast cancer

Abstract: Background: Previous studies have investigated the relationship between psychological flexibility and psychological well-being among university students. In addition to examining the relationship between these two variables, this study enhances our understanding about the process underlying the relationship between psychological flexibility and psychological well-being among women with breast cancer. The aim of the present study was to test the mediating role of self-compassion in the relationship between psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…27 Psychological Well-being Levels and Affecting Factors in the Women diagnosed as Breast Cancer Symptoms, diagnosis and treatment of cancer and side-effects of its treatment cause individuals to experience stress and disruption of functional capacity and psychological well-being. 17,28 Since the diagnosis of cancer is regarded as one of the most stressful events of life, psychological well-being of individuals living with cancer is of particular importance. Therefore, it is recommended that psychological well-being levels of individuals diagnosed as cancer should be regularly evaluated.…”
Section: Spousal Support Levels In the Women Diagnosed As Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…27 Psychological Well-being Levels and Affecting Factors in the Women diagnosed as Breast Cancer Symptoms, diagnosis and treatment of cancer and side-effects of its treatment cause individuals to experience stress and disruption of functional capacity and psychological well-being. 17,28 Since the diagnosis of cancer is regarded as one of the most stressful events of life, psychological well-being of individuals living with cancer is of particular importance. Therefore, it is recommended that psychological well-being levels of individuals diagnosed as cancer should be regularly evaluated.…”
Section: Spousal Support Levels In the Women Diagnosed As Breast Cancermentioning
confidence: 99%
“…They suggested that psychological exibility can foster self-compassion and ensure higher psychological well-being. 17 It is pointed out in the literature that spousal support is important for women with breast cancer to cope with and adapt to the disease psychologically and to reduce diagnosis-related psychological problems. 26 Krok and Telka reported a signi cant connection between spousal support and accepting the diagnosis of breast cancer and psychological well-being.…”
Section: Spousal Support Levels In the Women Diagnosed As Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation